2021
DOI: 10.1038/s41467-021-26100-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting endocytosis in CGRP+ nociceptors attenuates inflammatory pain-like behavior

Abstract: The advantage of locally applied anesthetics is that they are not associated with the many adverse effects, including addiction liability, of systemically administered analgesics. This therapeutic approach has two inherent pitfalls: specificity and a short duration of action. Here, we identified nociceptor endocytosis as a promising target for local, specific, and long-lasting treatment of inflammatory pain. We observed preferential expression of AP2α2, an α-subunit isoform of the AP2 complex, within CGRP+/IB4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 72 publications
(98 reference statements)
0
10
0
Order By: Relevance
“…There are some points that I would like to comment on: It would be nice if the authors discuss and compare these results with previous reports. For example, CGRP was known to play an important role in noxious heat sensitivity or inflammatory pain 1 , 2 . TrkB-positive neurons were also ablated to investigate its role in mechanical pain 3 .…”
mentioning
confidence: 99%
“…There are some points that I would like to comment on: It would be nice if the authors discuss and compare these results with previous reports. For example, CGRP was known to play an important role in noxious heat sensitivity or inflammatory pain 1 , 2 . TrkB-positive neurons were also ablated to investigate its role in mechanical pain 3 .…”
mentioning
confidence: 99%
“…2 CGRP+ve nociceptors express AP2α2, a key endocytosis protein that contributes to nociception. 28 Satellite glial cells of sensory ganglia were identified by immunostaining for GS. Dnm1 and Dnm3 mRNAs were expressed in neurons of DRG and TG (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The a subunit of the AP2 complex (AP2a2) is expressed in CGRP1ve nociceptors and AP2 small hairpin RNA (shRNA) suppressed nociception in mice. 28 However, the distribution of Dnm and AAK1 isoforms in nociceptive circuits is unknown, and their role in nociception is unexplored. We used genetic and pharmacological approaches to investigate the contribution of endocytosis to nociception.…”
Section: Introductionmentioning
confidence: 99%
“…While endocytosis is a critical mechanism in maintaining cell and thus host well-being, there is growing evidence that transient modulation is not only feasible but may have positive therapeutic outcomes. Chew et al ( 2020 ) report on blocking CME as an effective strategy to improve the clinical response to antibody dependent cellular cytotoxicity mediating antibodies in humans; Tremblay et al ( 2020 ) report that the dynamin inhibitor, dynole 34-4 is highly synergistic with existing chemotherapy in mouse models of T-ALL and AML; Powell et al ( 2021 ) report that endocytosis inhibition attenuates inflammatory pain like behaviour; and Jensen et al ( 2017 ) also reported on an endocytosis mediated effect as a viable therapeutic target for prolonged pain relief. While these findings should be considered positive, it is prudent to temper the enthusiasm that may be apparent with the realisation that the path to the clinic is long and winding.…”
Section: Discussionmentioning
confidence: 99%